2020
DOI: 10.1016/j.artd.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Spinopelvic Translation Is Combined With Pelvic Tilt During the Standing to Sitting Position: Pelvic Incidence Is a Key Factor in Patients Who Underwent THA

Abstract: Background: Sagittal spinopelvic translation (SSPT) is the horizontal distance from the hip center to the C7 plumb line (C7PL). SSPT is an important variable showing the overall patient balance in different functional positions which could affect the rate of hip instability. This study investigates the SSPT modification in patients who underwent total hip arthroplasty (THA). Methods: A total of 120 patients were assessed preoperatively and postoperatively on standing and sitting acquisitions (primary unilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
1
16
0
1
Order By: Relevance
“…In the discussions, three of the included studies seem to confirm the importance of global spinal alignment when planning THA to better understand the hip–spine relationship and identify those patients at high risk for MCs after THA. 3 , 11 , 12 In the data, however, the articles did not focus on spinal alignment. SVA was the only reported parameter that measures global sagittal alignment of the spine ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the discussions, three of the included studies seem to confirm the importance of global spinal alignment when planning THA to better understand the hip–spine relationship and identify those patients at high risk for MCs after THA. 3 , 11 , 12 In the data, however, the articles did not focus on spinal alignment. SVA was the only reported parameter that measures global sagittal alignment of the spine ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…found that patients with negative sitting SSPT are at higher risk for THA dislocation than patients with positive sitting SSPT. 3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the more fused levels, the more acetabular anteversion and inclination decrease (about 1° for each fused group for each value) [ 70 ]. Therefore, it has been proposed by Lazennec et al to evaluate lumbosacral junction using standing and sitting EOS imaging or radiographs in patients with spine fusion in THA planning and follow-up [ 71 , 72 , 73 ], but this attitude is not yet officially recommended.…”
Section: Imaging Follow-up Of Hamentioning
confidence: 99%